LncRNA REG1CP promotes tumorigenesis through an enhancer complex to recruit FANCJ helicase for REG3A transcription - Hamed Yari (Nature Portfolio, 2019)
The regenerating islet-derived (REG) protein family suppresses cell death and promotes cell proliferation. Here the authors report that the lncRNA REG1CP forms an RNA–DNA triplex at the promoter of REG3A gene to increase its expression.